Motivating your employees: rewards and recognition ([United States?] : Mill Valley, CA : Opus ; distributed by Kantola Productions, 2004)
Shows managers how to create a culture of achievement by celebrating accomplishments, large and small
Segment 1: Why recognition matters -- Segment 2: The foundations of recognition -- Segment 3: Fundamental principles -- Segment 4: Building a culture of recognition.
Presenter: Greg Kirsch.
DVD.
Keywords: Employee motivation; Personnel management; Motivation (Psychology)